A rua que acolhe, a rua que cura : equipe de Consultório na Rua como estratégia para atenção à pessoa com tuberculose - Alecrim, Tatiana Ferraz de Araújo (Universidade Federal de São Carlos, 2015)
The tuberculosis is characterized as a serious decease and affect the poorest regions of the world. Brazil occupies the 16th place in absolute numbers of cases. According to the Ministry of Health people on the streets are 67 times more likely to get sick from tuberculosis compared to the general population. This population is characterized by extreme poverty, interrupted or weak family bond and lack of residence, using the public places and degraded areas as their housing and sustenance. In 2011, the Ministry of Health implemented Street Clinic Teams as a care mode linked to primary health care, to address the different demands and health needs of the population in the streets. The teams offer “on the spot” and itinerantly, comprehensive health care for these people. The objective of this study was the analyses of sense production effect of the street clinic teams regarding to the care of people with tuberculosis. It is a qualitative assessment which took place at São Paulo’s central region. Six individuals took part in this study. The inclusion criteria: Team Nurses, Epidemiologic Surveillance Nurses, Technical Assessors who operate within street clinic teams, who agreed on signing the informed consent. A scripted semi-structured interview was applied for data collection, utilizing an audio recorder in all recorded interviews. The results emerged in four discursive blocks: characterization of care; service structure for TB patient’s care; incentives: cure x decease maintenance and the organization of work. The conclusion is that the care model in use by the investigate teams contribute to guaranteeing access to care, thus increasing early diagnosis, treatment, monitoring and cure of tuberculosis among that population.

La tuberculosis es caracterizada como enfermedad grave y acomete las regiones más pobres del mundo, Brasil ocupa el 16a posición en números absoluto de casos. El Ministerio de la Salud apunta que la población en situación de calle tiene de 48 al 67 veces más chances de enfermerse por TB cuando comparada a la población en general. Esta población es caracterizada por la pobreza extrema, bônus familiares interrumpidos o fragiles e inexistencia de hogares, se utiliza de los parques infantiles públicos y áreas degradadas para espacio de viviendas y sustento. Em 2011, El Ministerio de la Salud fue implementado Equipos de Consultorio en la Calle, como una modalidade vinculada a la Atención Primária, para abordar las diferentes demandas y necesidades de salud de la población de la calle. Los equipes ofertan en el locus y de forma itinerante la atención integral a la salud de esas personas. El objetivo de este estudio fue analisar los efectos de producción de los sentidos de los equipos de consultorio no cuidado a la persona en la calle con tuberculosis. Se trata de una investigación cualitativa, llevada a cabo en la región central de São Paulo. Participaron en el estudio seis sujetos. Los criterios de inclusión: enfermeras (la) equipo, enfermeros (as) responsables de la vigilancia epidemiológica, los gerentes y asesores técnicos que trabajan en los equipos de consultorio en la calle y acordaron firmar el término de consentimiento. Se utilizó una entrevista semi-estructurada para la recolección de datos y la función de grabadora se registraron todas las entrevistas. Los resultados discursivas surgieron cuatro bloques: caracterización de la atención; servicios de la estructura para el cuidado de las personas con tuberculosis; incentivos: curación x mantenimiento cura la enfermedad e la organización del trabajo. La conclusión El modelo de atención utilizado por los equipos investigados, ayudar a asegurar el acceso a la atención, se extiende el diagnóstico precoz, el tratamiento, el seguimiento y la cura de la tuberculosis en esta población.
Street Clinic Team as strategy for care to people with tuberculosis
Equipo de Oficina en la calle como estrategia para atención a lapersona com tuberculosis
Keywords: Equipes de consultório na rua; Tuberculose; Morador em situação de rua; Análise de discurso; Cuidado à pessoa com tuberculose; Street clinic teams; Tuberculosis; Resident in homeless condition; Discourse analysis; Care to the person with tuberculosis; CIENCIAS DA SAUDE